Mastering Metasploit : Take your penetration testing and IT security skills to a whole new level with the secrets of Metasploit, 3rd Edition. - Jaswal, Nipun (Packt Publishing Ltd, 2018)
Metasploit is a popular penetration testing framework that has one of the largest exploit databases around. This book will show you exactly how to prepare yourself for the attacks you will face every day by simulating real-world possibilities.